Finding & keeping great employees - Harris, Jim (American Management Association New YorkUS, 1999)
Describes 4 organizational core cultures namely: customer service; innovation; operational excellence; and spirit. Argues that if companies focus on one of these core cultures and align their staffing and retention processes to it, that they will attract valued employees. Describes best practices in staffing and retention that have been used by successful companies. Outlines a 6-step process for recruiting and retaining good employees.